Pemilihan Mesin Welding Otomatis Dengan Penerapan Value Engineering Dan Analitical Hierarchy Process - Moch Nuruddin; Deny Andesta (Semesta Teknika, 2008)
By chosening machine of welding automatic with Value Engineering, hence company can know which machine is which have high value and can improve production process specially to part of welding. With quality, quality of product which different each other hence consumer have to be clever in assessing and chosening reliable product. Because many company promoting its product with advertisements, so that make consumer interest to buying. This research aim to look for and analyse some alternative which can be made size measure in chosening machine of welding reliable automatic. Election of merk here there is three merk type for example Panasonic, Daihen, and Hitachi. From third this merk type will be selected which merk which have best quality. Result of got calculation, hence machine merk the selected is merk of Hitachi because this machine have high value and difference is expense of Rp 35 million compared to two other alternative. this Volts machine Pri equal to 380V, input pri 42,5KVA 23,5KW and current output 500A. If compared to this machine alternatives have value of Vn equal to 2,1.